PRACTICAL CONSIDERATIONS FOR THE IMPLEMENTATION OF MARKETING AUDIT AS STRATEGIC CONTROL (Polityki Europejskie, Finanse i Marketing)
The article discusses the problems of marketing control, understood as a function which tops the management cycle. The immediate aim of this article is to present the results of research on the use of marketing audit as a form of strategic marketing control, in particular, the indicated factors that affect the limitation of its use. Considerations on the theoretical aspect, as well as the analysis of empirical material of a secondary and primary nature, were conducted using the literature studies method and qualitative research methods. I presented the results of several studies directly devoted to the problems of implementing marketing audit against the background of analyzing the place of audit in the structure of marketing control. The research, although conducted at different times, in different markets and using different methods, undertook similar research topics, which allows, to some extent, a qualitative comparative analysis of their results. The presented results show that the degree of the use of marketing audit in economic practice still should be assessed as weak. Limiting factors for the use of marketing audit in enterprises include, first and foremost: restricting access to information necessary in the process of auditing, unawareness of the benefits resulting from the implementation of marketing audit, the unclear nature of marketing activities undertaken, and the fear of excessive organizational and financial burden.